Life cycle assessment of suberin and betulin production from birch bark - Yadav, Pooja; Korpinen, Risto; Räty, Tarmo; Korkalo, Pasi; Räsänen, Kati; Tienaho, Jenni; Saranpää, Pekka (Elsevier, 2024)
In this study, the environmental impact of suberin and betulin production from birch outer bark was evaluated using life-cycle assessment (LCA), and the ReCiPe 2016 Midpoint (H) method. The system boundary includes production of outer bark to betulin and suberin production, with bark residues utilized for energy production, including all inputs (materials and energy) and outputs. Three scenarios were used to examine using the allocation, extraction and hydrolysation of birch bark. In the baseline scenario (S1), the bark came from a biorefinery and processed in a separate unit, where the hydrolysed bark residue was incinerated to generate the heat; the integrated scenario (S2) and internal loop scenario (S3) considered production within a biorefinery but with different energy sources. The primary data were collected from laboratory experiments, and secondary data were taken from the literature and the ecoinvent 3.9.1 database. FU was 2.06 kg of polymer production that includes 1 kg of suberin and 1.06 kg of betulin production from the same process. The results showed that the global warming potential (GWP) for S1 was 15.5 kg CO2 eq. per FU, 16.22 kg CO2 eq./FU in S2 and 3.96 kg CO2 eq./FU in S3. According to our results, increasing the recycling rate of ethanol (50%, 90% and 98%) in the process and using wood-based energy from the biorefinery instead of Finnish mixed electricity resulted in a significant reduction in the most important environmental impact categories except land use.
Keywords: betulin; birch bark; cascading process; life-cycle assessment; environmental impacts; suberin